Buvusios Lietuvos Didžiosios Kunigaikštystės lenkų tautiniai demokratai ir lietuvių tautinis atgimimas XX amžiaus pradžioje - Dąbrowski, Przemyslaw (Lietuvos istorijos studijos, 2011)
The fundamentals of the Lithuanian national revival date back to the eighties of the 19th century when in the environment of Lithuanian intellectuals a conception of publishing a newspaper in the Lithuanian language and printed in the Latin alphabet arose. Among the many persons involved in the implementation of this project, doctor Jonas Basanavičius played an outstanding role; he did not put up with failures in obtaining the publishing concession for the territory of the Russian Empire and decided to do it in Prussian Lithuania - in Ragainė and consequently to smuggle the copies of the newspaper across the border to the area of Great Lithuania. "Aušra" - "Jutrzenka" was supposed to become the "daybreak of the national revival of Lithuania". National democrats in Vilnius treated the Lithuanian national movement rather in transitional categories, as a long-term action or aspirations of getting wide autonomy in the future. Lithuania, in the territorial-historical aspect, was treated as a body formed by all nationalities inhabiting this area, favouring simultaneously the equality of rights of them all. They were critical only about the actions of Lithuanian activists - "litwomans".